Withdrawal From International Treaties And Its Impact On Inter-State Relations - أحمد, بسام (Latakia University Journal - Economic and Legal Sciences Series, 2020)
Some countries use existing international treaties as a way to pressure on the states parties, by threatening to withdraw from them or actually withdraw from them, as part of a formal plan. The United States has consistently pursued its approach with a series of steps to withdraw from multilateral bodies and treaties including the United Nations Educational, Cultural and Scientific Organization, the United Nations Human Rights Council, the nuclear agreement with Iran, and the Paris Agreement on climate change, withdrawal from bilateral treaties, which raises legal chaos, undermines the development of international law, and makes the world more dangerous. The license to withdraw from important international treaties, Even if an explicit text was mentioned on it, must be used in the narrowest limits, for strong justifications, taking into account the strict application of the conditions and procedures for withdrawal, and the need to adhere to the principles of international law to govern the relationship regulated by Treaties from which withdrawal was done. Given the danger of withdrawal from international treaties on international peace and security, we will highlight this unilateral act in accordance with the Vienna Treaty, as stated in some international treaties and show its distinction from other cases of expiration of treaties and explain its effect on international relations, and warn against using legal means for political purposes.